The Shift from Tangible to Intangible Assets: Valuation and Management of Intellectual Property in Modern Business (Based on the Example of the Post-Industrial Economy) - Bakhriddinova Aziza Toxir Kizi (Uzbekistan Open Conference, 2025)
The article examines the global economic shift from tangible to intangible assets. Special attention is given to intellectual property as a key factor of competitiveness in the post-industrial economy. The study analyzes modern methods of intangible asset valuation, management mechanisms, and their impact on business value. Examples of successful strategies of companies using intellectual resources as a basis for sustainable development are presented.
Keywords: Intangible assets; intellectual property; valuation; post-industrial economy; knowledge management